Adult‐onset immunodeficiency due to anti‐interferon‐gamma autoantibody‐associated Sweet syndrome: A distinctive entity. Issue 1 (21st October 2021) - Kiratikanon, Salin; Phinyo, Phichayut; Rujiwetpongstorn, Rujira; Patumanond, Jayanton; Tungphaisal, Veeraphol; Mahanupab, Pongsak; Chaiwarith, Romanee; Tovanabutra, Napatra; Chiewchanvit, Siri; Chuamanochan, Mati
Abstract: Sweet syndrome (SS) has been increasingly reported in patients with adult‐onset immunodeficiency (AOID) due to anti‐interferon‐γ autoantibody who also have concomitant opportunistic infections, especially disseminated non‐tuberculous mycobacterial infection (dNTMI). A retrospective study retrieving data from 2011 through 2020 was conducted. We compared clinical characteristics of SS with and without AOID and generated the prediction model and examined the interaction between AOID and dNTMI in the occurrence of SS. Lymphadenopathy, pustular lesions, and leukocytosis are the significant predictors for AOID‐associated SS. Adjusted risk differences were 0.58 (95% confidence interval [CI], 0.33–0.83), 0.21 (95% CI, 0.02–0.39), and 0.24 (95% CI, 0.01–0.47), respectively. Based on the analysis of aggregated cross‐sectional data, both the overall and the direct effect of AOID increased the prevalence of SS. The indirect effect of AOID on the occurrence of SS might also be mediated through dNTMI or other common opportunistic infections. In addition, there was a trend of positive additive interaction between AOID and dNTMI. Although the test of additive interaction did not reveal statistically significant results, a deviation from additivity of isolated effects might suggest potential causal interaction between AOID and dNTMI. The distinctive clinical syndrome comprising lymphadenopathy, pustular lesions, and leukocytosis in patients with SS should raise the awareness of clinicians to the potential of underlying AOID.